Fine structure in the α decay of 218At - Cubiss, James; Fink, Daniel (Physical review, 2019)
An α-decay study of 218At was performed at the CERN-ISOLDE facility. Laser-ionized beams of 218At were mass separated and implanted into an α-γ detection setup. Coincidence α-γ data were collected for the first time and a more precise half-life value of T1/2 = 1.27(6) s was measured. A new α-decay scheme was deduced based on the extracted reduced α-decay widths for fine-structure decays. The results from this work lead to a preferred spin and parity assignment of Jπ = (3−); however, Jπ = (2)− cannot be fully excluded.